Green technology and economic growth : Evidence from OECD countries / Muhammad Nurhusaini Haizad - Haizad, Muhammad Nurhusaini (Universiti Teknologi Mara Perlis, 2020)
The aim of this study is to determine the relationship between green technology and economic growth in OECD countries. Panel data of 36 OECD countries have been utilized. Dependent variables in this study is Economic growth, while independent variables are green technology, carbon emission, energy consumption and capital formation. This study employed, panel granger causality test and panel regression analysis to analyze the data. The findings reveal green technology and capital formation are negatively significant in effecting economic growth, while CO2 emission is positively significant in influencing economic growth. Therefore we can conclude that the application of renewable energy does not increases the economic growth of OECD countries.